A comparison between EAM interatomic potentials for Al and Ni: from high to low coordination systems - Peláez, Santiago; García Mochales, Pedro; Serena, Pedro (Ciencia)
Two different kinds of interatomic potentials within the Embedded Atom Method (EAM) have been used to study several properties of selected crystalline structures and nanowire configurations (ordered and helical) for Al and Ni based systems. Results clearly indicate the existence of increasing differences in the calculated quantities (cohesive energy and geometrical parameters) as the atomic coordination number decreases. This implies that EAM potentials must be cautiously used when analyzing low coordination systems such as metallic nanowires.